Investigations into Metal Leaching from Polystyrene‐Supported Rhodium Catalysts. Issue 2 (16th November 2015) - Fischer, Christian; Thede, Richard; Baumann, Wolfgang; Drexler, Hans‐Joachim; König, Anja; Heller, Detlef
Abstract: The anchoring of molecularly well‐defined Rh complexes on a solid support allows the combination of the advantages of homogeneous catalysis with the benefit of catalyst recycling offered by heterogeneous catalysis. Unfortunately, the common approach to attach the soluble Rh catalyst onto a variety of polystyrene supports has not in general led to useful catalysts, and a major problem is metal leaching into the solution. We report herein that, besides the binding of the Rh catalysts to the polymeric matrix, in principle η 6 ‐aromatic complexes can also be formed, as shown by NMR spectroscopy and XRD. The stability constants of such complexes for styrene and soluble polystyrenes (PS4000, 38.4 monomers and PS30000, 288 monomers) have been measured by UV/Vis spectroscopic titrations. The establishment of equilibrium with the Rh‐solvent complex is very rapid to the point that, after the anchoring of the catalyst to the polystyrene matrix, the rinsing of the material with solvent during work‐up causes part of the Rh coordinated originally as an aromatic complex to be washed away. Abstract : Teaching from leaching : The recombination of homogeneous with heterogeneous catalysis means to anchor a molecularly well‐defined metal complex on a solid support. In the case of Rh‐mediated catalysis, a heterogeneous catalyst often leads to a reduced activity compared to the homogenous analogue. Likewise, a loss of Rh is observed during the reprocessing of the resin. This work provides a possible explanation for these phenomena that originate in the η 6 ‐coordination of the Rh to aromatic rings within the support.